Foundations of theoretical soil mechanics - Harr, M. E. (McGraw-Hill, 1966)
Fundamental relations - Stresses and displacements in soil mass as elastic body - Settlement and coonsolidation - Soil strength - Stability of soil structures-Conventional methods - Limiting equilibrium of soil structures - Appendix.